2004
DOI: 10.1179/147842204x2899
|View full text |Cite
|
Sign up to set email alerts
|

Role of anaerobic and aerobic bacteria in localised corrosion: field and laboratory morphological study

Abstract: Bacterial evidence was found in the biofilm deposited on the surface of an API X52 steel coupon following exposure to flowing seawater within a pipeline for 60 days. Extensive corrosion pitting was observed on the steel surface after removing the biofilm. Several types of anaerobic and aerobic bacteria were isolated from the biofilm. The anaerobic bacteria were cultured and grown in API RP 38 culture medium and the aerobic bacteria were grown in a general heterotrophic culture medium. The morphological and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Robert Jefrey and Robert E Merchers (2002) found a globular corrosion product at the surface of the samples after certain period of corrosion test. Analysis on this product shows that this globular corrosion product is iron hydroxide [6]. This type of hydroxide was found also at the sample no 16 (figure 2) that was immersed for 21 days as shown on figure 10.…”
Section: Flat Areamentioning
confidence: 60%
“…Robert Jefrey and Robert E Merchers (2002) found a globular corrosion product at the surface of the samples after certain period of corrosion test. Analysis on this product shows that this globular corrosion product is iron hydroxide [6]. This type of hydroxide was found also at the sample no 16 (figure 2) that was immersed for 21 days as shown on figure 10.…”
Section: Flat Areamentioning
confidence: 60%
“…Romero et al . () suggested that the formation of a biofilm on a metal surface changed local conditions and associated changes in gradients of pH, dissolved oxygen, chloride and sulphate, which then created conditions associated with localised corrosion. Xu et al .…”
Section: Resultsmentioning
confidence: 99%
“…One likely reason is that EPS form a layer on the surface, which cuts off the oxygen supply to the cells that are directly in contact with the metal surface, hence creating anaerobic conditions, which could induce corrosion on metal surfaces having biofilms. Romero et al (2004) suggested that the formation of a biofilm on a metal surface changed local conditions and associated changes in gradients of pH, dissolved oxygen, chloride and sulphate, which then created conditions associated with localised corrosion. Xu et al (1999) suggested that biofilms result in pitting, crevice corrosion and stress corrosion cracking due to the metabolic processes of the living organism.…”
Section: Observations Related To the Elemental Analysis Of Ss 304 Andmentioning
confidence: 99%
“…Robert Jefrey and Robert E Merchers (2002) found a globular corrosion product at the surface of the samples after certain period of corrosion test. Analysis on this product shows that this globular corrosion product is iron hydroxide [6]. This type of hydroxide Figure 10.…”
Section: Discussionmentioning
confidence: 96%